Television on demand curatorial culture and the transformation of TV - Robinson, MJ (Mary Jean) 1967- (Bloomsbury Academic, 2017)
"Interrogates the challenges facing the producers and distributors of America's episodic television in a world that increasingly encourages and enables customized, on demand viewing"--